Friction stir welding of AZ31B magnesium alloy with ER4043 aluminium alloy filler - H., Tarizan; M., Ishak; Quazi, M. M.; Qaban, A. (2019)
Magnesium Alloys (Mg) are well-known for the lightweight structural behaviour that makes them an excellent choice in applications requiring higher fuel efficiency such as in the automotive and aircraft industries. Their usage is limited in such structural applications owing to their poor weld ability. Formation of defects such as porosities, loss of alloying elements and distortion are common when conventional fusion welding techniques are employed. However, friction stir welding a solid-state joining can be used to join two materials without any risk of melting. This research is focused on friction stir butt-joining of 2mm thick AZ31B Mg alloy with the aid of aluminium (Al) alloy filler (ER4043). A tapered cylindrical shaped tool that was made from H13 tool steel was used with a tool tilt angle of 1 ̊. By applying a rotational tool speed (RS) of 1200 rpm and welding travel speed (WS) of 90 mm/min an ultimate tensile strength of 188.8 MPa was obtained contributing to a joint efficiency of 72.6 %. The maximum hardness in the stirred zone (SZ) was found to be 70 Hv, while in the thermo-mechanically mixed zone (TMAZ) was 66 Hv followed by a significant reduction in the heat-affected zone (HAZ) to a minimum of 57 Hv. The failure occurred between SZ and HAZ retreating side owing to weaker and complex intercalated microstructures comprising of swirls and vortexes that were indicative of a flow pattern of dissimilar metals.